All-Trans-Retinoic Acid Suppresses Neointimal Hyperplasia and Inhibits Vascular Smooth Muscle Cell Proliferation and Migration via Activation of AMPK Signaling Pathway - Zhang, Jingzhi; Deng, Bo; Jiang, Xiaoli; Cai, Min; Liu, Ningning; Zhang, Shuangwei; Tan, Yongzhen; Huang, Guiqiong; Jin, Wen; Liu, Bin; Liu, Shiming (Frontiers in Pharmacology, 2019)
The proliferation and migration of vascular smooth muscle cells (VSMC) is extensively involved in pathogenesis of neointimal hyperplasia. All-trans-retinoic acid (ATRA) is a natural metabolite of vitamin A. Here, we investigated the involvement of AMP-activated protein kinase (AMPK) in the anti-neointimal hyperplasia effects of ATRA. We found that treatment with ATRA significantly reduced neointimal hyperplasia in the left common carotid artery ligation mouse model. ATRA reduced the proliferation and migration of VSMC, A7r5 and HASMC cell lines. Our results also demonstrated that ATRA altered the expression of proliferation-related proteins, including CyclinD1, CyclinD3, CyclinA2, CDK2, CDK4, and CDK6 in VSMC. ATRA dose-dependently enhanced the phosphorylation level of AMPKα (Thr172) in the left common carotid artery of experimental mice. Also, the phosphorylation level of AMPKα in A7r5 and HASMC was significantly increased. In addition, ATRA dose-dependently reduced the phosphorylation levels of mTOR and mTOR target proteins p70 S6 kinase (p70S6K) and 4E-binding protein 1 (4EBP1) in A7r5 and HASMC. Notably, the inhibition of AMPKα by AMPK inhibitor (compound C) negated the protective effect of ATRA on VSMC proliferation in A7r5. Also, knockdown of AMPKα by siRNA partly abolished the anti-proliferative and anti-migratory effects of ATRA in HASMC. Molecular docking analysis showed that ATRA could dock to the agonist binding site of AMPK, and the binding energy between AMPK and ATRA was -7.91 kcal/mol. Molecular dynamics simulations showed that the binding of AMPK-ATRA was stable. These data demonstrated that ATRA might inhibit neointimal hyperplasia and suppress VSMC proliferation and migration by direct activation of AMPK and inhibition of mTOR signaling.